Acropetal and basipetal cardenolide transport in Erysimum cheiranthoides (wormseed wallflower). (December 2021) - Alani, Martin L.; Younkin, Gordon C.; Mirzaei, Mahdieh; Kumar, Pavan; Jander, Georg
Abstract: Plant specialized metabolites are often subject to within-plant transport and have tissue-specific distribution patterns. Among plants in the Brassicaceae, the genus Erysimum is unique in producing not only glucosinolates but also cardenolides. Ten cardenolides were detected with varying abundance in different tissues of Erysimum cheiranthoides L (Brassicaceae; wormseed wallflower). As is predicted by the optimal defense theory, cardenolides were most abundant in young leaves and reproductive tissues. The lowest concentrations were observed in senescing leaves and roots. Crosses between wildtype E. cheiranthoides and a mutant line with an altered cardenolide profile showed that the seed cardenolide phenotype is determined entirely by the maternal genotype. Prior to the development of the first true leaves, seedling cotyledons also had the maternal cardenolide profile. Hypocotyl grafting experiments showed that the root cardenolide profile is determined entirely by the aboveground plant genotype. In further grafting experiments, there was no evidence of cardenolide transport into the leaves, but a mixed cardenolide profile was observed in the stems and inflorescences of plants that had been grafted at vegetative and flowering growth stages, respectively. Together, these results indicate that E. cheiranthoides leaves are a site of cardenolide biosynthesis. Graphical abstract: Cardiac glycosides in Erysimum cheiranthoides (Brassicaceae L; wormseed wallflower) are transported from leaves to roots and reproductive tissue. Image 1 Highlights: Cardenolide content of Erysimum cheiranthoides (wormseed wallflower) varies by tissue type. The aboveground plant genotype determines the root cardenolide phenotype. Cardenolides are transported from maternal tissue to developing seeds. Cotyledons have a cardenolide phenotype that is determined by the maternal plant. Seedling cardenolide biosynthesis is initiated with the emergence of true leaves.